Making a Timely Diagnosis of Pulmonary Tuberculosis - Richard Long (Canadian Respiratory Journal)
Making a timely diagnosis of adult-type pulmonary tuberculosis (TB) is critical to interrupting transmission and optimizing treatment outcomes. A hypothesis based on clinical experience is that a timely diagnosis may be made by addressing seven clinical rubrics: six related to history, one to the laboratory. Responses may be considered to be part of a clinical heuristic for making a timely diagnosis of pulmonary TB. The larger the number of affirmative responses, the more likely the diagnosis, although it is probable some questions carry more weight than others. The radiograph is key and may almost be considered to be confirmatory of the history. Collectively, the responses should prompt suspicion of pulmonary TB – submission of sputum for acid-fast bacilli smear and culture, and respiratory isolation.